PENGARUH TINGKAT KETERLIBATAN PEMAIN DAN TINGKAT KETERLIBATAN KOMUNITAS ONLINE TERHADAP LOYALITAS PEMAIN GAME GACHA HONKAI: STAR RAIL DI INDONESIA - Angwar Venus Aurelia; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Gacha monetization strategies in mobile games have sparked debates regarding their similarities to gambling practices, the risk of addiction, and potential financial, psychological, and social losses. Despite these controversies, gacha games are capable of creating long-term play commitments among a massive global player base. This phenomenon reflects gacha player loyalty, which can be influenced by the interactions between players and the game, as well as with other players. This study aims to determine the extent of the influence of player engagement level and online community engagement level on player loyalty among Honkai: Star Rail gacha players in Indonesia. Drawing on Social Exchange Theory and Social Identity Theory, this study analyzed 398 respondents selected through purposive sampling and analyzed using simple linear regression via SPSS 25. This study found that the level of player engagement has a significant influence on gacha player loyalty, contributing 43.5% with an effect size of 0.498. This indicates that the higher the level of player engagement, the higher the loyalty of gacha game players. Furthermore, the level of online community engagement also significantly influences gacha player loyalty, contributing 17.5% with an effect size of 0.255. This shows that higher online community engagement leads to higher player loyalty. The author suggests that companies should design more varied in-game events and interactive online community ecosystems to maintain and increase player loyalty for Honkai: Star Rail in Indonesia.